Acantholimon davisii (Plumbaginaceae), a new specific name for the Turkish endemic A. caryophyllaceum subsp. parviflorum - Akaydin Gali̇p; Crespo, Manuel B. (Phytotaxa, 2018)
Acantholimon Boissier (1846: 69) nom. cons., was first described to include perennial, densely or laxly pulvinate subshrubs, mostly thorny and cushion-forming. The genus currently contains about 200 taxa, mainly distributed from SE-Europe to C-Asia (see e.g., Kubitzki 1993). The main distribution centres of the genus are in the eastern Mediterranean and the Irano-Turanian regions (Bokhari 1970, Yıldırım & Crespo 2014), where many endemics occur. Taxa in Acantholimon have considerable ecological and economic importance, mostly as ornamental plants because their long-lasting and nicely coloured flowers (Doǧan & Akaydın 2004).